Sustainability Environmental Performance Future Investment for Company Value - Dwianto, Agus; Puspitasari, Diana; A'yun, Annisa Qurrota; Sulistyawati, Ardiani Ika; Pugara, Ade (Journal of Ecohumanism, 2024)
This study investigates the financial dynamics of 182 manufacturing companies listed on the Indonesia Stock Exchange during the period 2019 to 2022, amid the COVID-19 pandemic. This study uses a quantitative approach using SPSS for regression analysis. The dataset covers the turbulent years of the COVID-19 pandemic, providing insights into the resilience and adaptability of companies during this period. This study reveals that while capital structure and dividend policy do not significantly affect firm value, firm growth, profitability and investment decisions exert a differential influence. Notably, environmental performance moderates the impact of growth and profitability on firm value, but does not significantly affect relationships involving capital structure, dividend policy, or investment decisions. This research contributes to the growing landscape of financial analysis by incorporating environmental considerations as a moderating factor. It underscores the importance of sustainable practices in improving financial performance and firm value, especially in the context of global crises such as the COVID-19 pandemic.